2023
DOI: 10.1093/bioinformatics/btad446
|View full text |Cite
|
Sign up to set email alerts
|

Position-Specific Enrichment Ratio Matrix scores predict antibody variant properties from deep sequencing data

Abstract: Motivation Deep sequencing of antibody and related protein libraries after phage or yeast-surface display sorting is widely used to identify variants with increased affinity, specificity and/or improvements in key biophysical properties. Conventional approaches for identifying optimal variants typically use the frequencies of observation in enriched libraries or the corresponding enrichment ratios. However, these approaches disregard the vast majority of deep sequencing data and often fail to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
2
1
0
Order By: Relevance
“…This is supported by a body of evidence from other protein families 51,52 showing the sparseness of functional protein landscapes 53 . We also found that these sequence-binding fitness landscapes were most consistent with one-body or at most twobody interactions, consistent with recent protein engineering literature [54][55][56] . The resulting implication is that sampling of a small percentage of potential variants is sufficient for reconstruction of fitness landscapes.…”
Section: Discussionsupporting
confidence: 89%
“…This is supported by a body of evidence from other protein families 51,52 showing the sparseness of functional protein landscapes 53 . We also found that these sequence-binding fitness landscapes were most consistent with one-body or at most twobody interactions, consistent with recent protein engineering literature [54][55][56] . The resulting implication is that sampling of a small percentage of potential variants is sufficient for reconstruction of fitness landscapes.…”
Section: Discussionsupporting
confidence: 89%
“…This is supported by a body of evidence from other protein families 51,52 showing the sparseness of functional protein landscapes 53 . We also found that these sequence-binding fitness landscapes were most consistent with one-body or at most two-body interactions, consistent with recent protein engineering literature [54][55][56] . The resulting implication is that sampling of a small percentage of potential variants is sufficient for reconstruction of fitness landscapes.…”
Section: Discussionsupporting
confidence: 89%
“…Mutational maps of antibodies can be created as position specific scoring matrices (PSSM) [18], or creating multiple sequence alignments (MSA) of millions of NGS sequences sharing a single germline origin [19,20]. Other studies have demonstrated the feasibility of gene agnostic language models of the human antibody space [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%